Some factors affecting financial distress in telecommunication companies in Southeast Asia - Kristanti, Farida Titik; Pancawitri, Sekarayu (Business: Theory and Practice, 2024)
People who have lost their jobs are affected by the Covid-19 epidemic, which lowers demand and prevents them from updating daily used internet services. A company’s deteriorating financial health may be a warning indication of impending financial trouble. With company size serving as a moderating variable, the purpose of this study is to ascertain the impact of earnings management, corporate strategy, the board of directors, and debt asset ratio on financial distress. Ten telecoms businesses in Southeast Asia were the result of the purposive sampling technique from 2013 to 2022. Both logistic regression and moderated regression analysis are used in this study. These findings show how financial hardship simultaneously affects management of earnings, corporate strategy, the board of directors, and the debt asset ratio. However, financial distress is partially impacted negatively by the factors debt asset ratio, board of directors, and earnings management. The business strategy variable is now untouched by financial difficulties. Financial distress is not significantly impacted by company size, which moderating the debt asset ratio from the regression analysis.